Nanoplatform‐Enabled Genetic Interventions for Central Nervous System Disorders: Advances in Delivery Strategies and Therapeutic Potential - Fuming Liang; Shizhen Cui; Jing Yang; Zhaohui He; Ling Zhu (Advanced Genetics, 2025)
Abstract Central nervous system (CNS) disorders are driven by complex genetic and epigenetic factors. While gene‐based interventions (siRNA, mRNA, CRISPR systems, etc.) hold transformative potential, their clinical application is severely constrained by inefficient delivery, especially across the blood‐brain barrier. Nanocarriers have emerged as transformative platforms that overcome these challenges by enabling efficient BBB penetration while ensuring precise biodistribution control and enhanced therapeutic payload protection. This review explores recent advances in nanoplatform‐enabled genetic intervention that overcome the delivery challenges through innovative engineering approaches. We discuss the genetic and epigenetic mechanisms underlying major CNS pathologies, the current limitations of free nucleic acid therapeutics, the development of advanced nanoplatforms that achieve blood‐brain barrier penetration and targeted delivery. We further also evaluate therapeutic prospects across disease models while addressing translational challenges in stability, targeting specificity, and manufacturing scalability. By integrating fundamental research with preclinical applications, this review provides both a theoretical framework and practical roadmap for developing next‐generation nanotherapeutics for CNS genetic medicine.